Positioning of the Amalgamated Territorial Communities of Ukraine through the Sustainable Development in the Conditions of Military Actions - Budnikevich, Iryna; Kolomytseva, Olena; Rohozian, Yuliia; Krupenna, Inga; Zablodska, Daria (Problemy Ekorozwoju, 2021)
The article summarizes and analyses the scientific approaches to the determination and systematization of the positioning parameters of local level territories. The authors determined and systematized the positioning parameters of the amalgamated territorial communities in Ukraine through the prism of sustainable development elements in the conditions of military operations to form the most effective position of a particular community among other administrative-territorial units of the first level. Based on the results of the analysis of the positioning status in Ukraine, the Ukrainian regions were clustered by the number of ATCs that determined the direction of positioning. It is proved that each of the ATC deserves a worthy positioning of its territory in the eyes of the key stakeholders of its development. However, the communities of precisely Donets`k and Luhans`k regions will do just that, since they continue to receive losses from hostilities unfolding nearby.